Genetic structure of glyphosate-resistant ( R ) and glyphosate-susceptible ( S ) populations of Eleusine indica (L.) Gaertn from Peninsular Malaysia - Chong, Ju Lian; Ratnam, Wickneswari; Sahid, Ismail; Surif, Salmijah (Penerbit Universiti Sains Malaysia, 2004)
Glyphosate is the world’s most widely used herbicide, accounting for 11 % of worldwide herbicide sales (Powles et al., 1997). As a nonselective herbicide with no soil activity (Grossbard & Atkinson 1985), it is an ideal herbicide to control a broad range of weed species. In Malaysia, glyphosate is used to control various weed species growing in oil palm and rubber plantations. In some instances, multiple treatments have been carried out continuously for several years.